Hydroxylation of 2-methylnaphthalene to 2-methylnaphthoquinone over TI-substituted catalysis - Rose, Jamey (Stellenbosch : University of Stellenbosch, 2010)
Thesis (MScEng (Process Engineering))--University of Stellenbosch, 2010.